The Banana Festival in the Colombian Urabá: Culture and Tradition [la Fiesta del Banano en el Urabá Colombiano: Cultura y Tradición] - Florez-Mendez, J (Institute of Advanced Studies, University of Santiago de Chile, 2021)
Colombia, thanks to its geographical location, has advantages for the production and marketing of various fruits, many of which participate in international markets, as is the case of bananas. The most important banana zone in Colombia is located in the Urabá region with a vast area of banana cultivation, generating a positive economic impact both nationally and regionally. It is in the municipality of Apartadó where the most important festival of Colombian bananas takes place, a festival attended by locals and foreigners and where various activities are developed around the cultivation of bananas. The objective of this article is to make known the cultural and gastronomic samples developed in these festivities as well as to recognize the fruit of the banana as an invaluable sample of culture and tradition in Colombia. © 2021 Revista Iberoamericana de Viticultura Agroindustria y Ruralidad. All rights reserved.